Diagnostics of D.C. Starter Generators While Using Fuzzy Logic Theory - A. A. Lobaty; A. A. Sheinikov; A. N. Belegov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2011)
Methodology for sparking control in generator brush contact has been developed on the basis of the proposed fuzzy diagnostic model for ad.c.starter-generator and complex processing of diagnostic data. The paper provides investigation results, namely: dependence of voltage parameters  in an external generator circuit on collector sparking intensity.